Melatonin mediates the reversibility of brain hyperphosphorylated tau protein induced by synthetic torpor in rats. (1st February 2022) - Luppi, Marco; Hitrec, Timna; Cerri, Matteo; Occhinegro, Alessandra; Piscitiello, Emiliana; Squarcio, Fabio; Moshari, Mahshad; Aminpour, Maral; Tuszynski, Jack A.; Cavaglià, Marco; Amici, Roberto
Abstract: Background: The hyperphosphorylation of tau protein (PPtau) in the brain is the main pathophysiological marker of tauopathies. Recently was found that when induced by a "synthetic torpor" (ST) 1 condition (induced on rats), PPtau accumulations is reversible, as observed in hibernators 2 . Thus, ST uncover a latent physiological mechanism able to cope with PPtau and not specifically evolved with hibernation. Aim of the present work was to describe it. Methods: We induced ST as already reported 2 on 12 Sprague‐Dawley rats. Hippocampal and plasma samples were collected at the following experimental conditions: nadir of hypothermia (N); early recovery (ER), as soon as animals reached normothermia following N; 6h following ER (R6). Control (C) animals were also included. Levels of AT8 (p[S020/T205]‐tau), p[S9]‐GSK3β (inhibited form of the main kinase targeting tau) and plasma melatonin were determined. To better understand in vivo experimental results, we performed in silico simulations of melatonin‐tubulin interactions 3 . Results: Figure 1 shows, at N, a huge amount of AT8 and high levels of p[S9]‐GSK3β and melatonin in respect to C. All factors returned to normal at R6. These paradoxical results (i.e. the coexistence of high levels of PPtau and p[S9]‐GSK3β) could be interpreted considering the destabilization of microtubules (MTs) induced by hypothermia as the main trigger of the whole process, then eliciting a neuroprotective physiological response mediated by melatonin, also interacting with MTs. To sustain this hypothesis, we also provide computational analysis of the microtubule stability as a function of temperature and other factors, such as melatonin binding. The molecular docking simulation shows that melatonin did not bind to 1sa0 structure, but it binds to one site of 1jff structure on the α‐tubulin monomer (Figure 2). This is further elucidated using a molecular fingerprint representation (Figure 3), showing the binding site of melatonin with respect to those well‐known binding locations. Conclusions: Our results could pave the way for an effective new strategy to contrast tauopathies, with next‐step studies aimed to pharmacologically interacting with this process at physiological temperature. References: (1) Luppi et al. Front Neuroanat 2019, 13:57; (2) Stieler et al. PLoS One 2011, 6: e14530. 3 Craddock, et al. Sci Reports 2017, 7:1.